Trifluridine/tipiracil in combination with local therapy may be a favorable option for refractory metastatic colorectal cancer patients: A case report. Issue 43 (23rd October 2020) - Lin, Yu-Lin; Liu, Kao-Lang; Lin, Been-Ren
Abstract: Rationale: Currently, the 5-year survival rate remains poor for patients with metastatic colorectal cancer (mCRC), and the purpose of therapy is to prolong survival while maintaining the quality of life. Trifluridine/tipiracil, an oral drug combining trifluorothymidine and a thymidine phosphorylase inhibitor, is indicated as salvage therapy for mCRC patients who have progressed after all available regimens. Combination of local treatments with systemic therapy such as trifluridine/tipiracil represents an apt management strategy for mCRC patients. Patient concerns: A 72-year-old man diagnosed with stage IV rectal adenocarcinoma (KRAS mutation) with peritoneal carcinomatosis and liver metastases developed resistance to 2 lines of treatment (bevacizumab/irinotecan/S-1 and bevacizumab/oxaliplatin/HDFL [high-dose 24-hour infusion of 5-fluorouracil and leucovorin regimen]) within 5 months. Diagnosis: Refractory stage IV rectal adenocarcinoma. Interventions: Systemic treatment of trifluridine/tipiracil has been given for approximately 15 months in addition to radiotherapy, Yttrium-90 radioembolization, and trans-arterial chemoembolization for peritoneal and liver metastases. Outcomes: After 15 months, the patient was still taking trifluridine/tipiracil for disease control with a good quality of life. Lessons: Trifluridine/tipiracil plus other appropriate local therapy may significantly prolong patients survival with a satisfactory quality of life for patients with refractory mCRC. The favorable safety profile of trifluridine/tipiracil renders it a suitable option to be combined with other local therapies for metastatic lesions.